Rediseño del Terminal Terrestre de Durán para la mejora del confort térmico mediante la aplicación de criterios bioclimáticos - Cedeño Jaramillo, Andy Bryan (2025)
The Durán Canton, located in the province of Guayas, exactly located on the banks of the estuary of that name, is a strategic point that allows the connection between the Sierra and the Coast. It currently has approximately 303,910 inhabitants, experiencing an abundant wave of population in recent decades, allowing its urban and commercial core to reflect an active life and potential in its daily activities. This project entitled Redesign of the Durán land terminal to improve thermal comfort through the application of bioclimatic criteria, aims to propose a solution to the problem encountered, the lack of maintenance in its infrastructure allows us to collect information and know the consequences that currently exist in the building in order to provide a comfortable stay to users...........